Pengaruh Minat Belajar dan Kepercayaan Diri terhadap Hasil Belajar Kognitif Matematis pada Siswa SMK Negeri 7 Kabupaten Tangerang - Charlos E. P. L. Gaol; Nerru Pranuta Murnaka; Ayatul Ulya (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
This study was motivated by the low mathematics learning outcomes of vocational high school students, which are influenced by affective factors, particularly learning interest and self-confidence. Mathematics plays a crucial role in developing students’ logical, critical, and systematic thinking skills; therefore, successful mathematics learning constitutes an essential component of vocational education. The research problem focused on the influence of learning interest and self-confidence on the mathematical cognitive learning outcomes of eleventh-grade students at SMK Negeri 7 Kabupaten Tangerang. The study employed a quantitative approach with a correlational survey design. The research sample consisted of 129 students selected through cluster sampling techniques. Data were collected through Likert-scale questionnaires and documentation of students’ mathematics scores. Data analysis was conducted using descriptive statistics, Pearson correlation, and multiple linear regression with the assistance of SPSS software. The findings revealed that learning interest did not have a significant effect on mathematics learning outcomes, contributing only 1.1%, whereas self-confidence had a significant effect with a contribution of 10.8%. Simultaneous testing demonstrated that learning interest and self-confidence collectively exerted a significant influence on mathematics learning outcomes with a contribution of 13.8%. The findings indicate that self-confidence is a more dominant affective factor than learning interest in improving the mathematical cognitive learning outcomes of vocational high school students. The novelty of this study lies in the finding that the vocational practice-oriented characteristics of vocational high school students cause learning interest not to directly influence mathematics learning outcomes, while self-confidence emerges as a more determining factor in students’ academic achievement. The results of this study are expected to serve as a foundation for developing mathematics learning strategies that are more oriented toward strengthening students’ psychological aspects.